Actuation delay compensation of robots in semi-physical test - Zhang, Xiao; He, Yun; Xu, Zhigang; Jiang, Zainan; Liu, Yong; Feng, Wenbo; Wu, Junwu (Frontiers in Neurorobotics, 2023)
In general, the traditional spacecraft semi-physical docking tests include the evaluation of docking and separation performance. However, these tests often rely on "specific" equipment, such as specially designed actuators and fast-response hydraulic systems, to meet the stringent dynamic response requirements of semi-physical testing. In this paper, a novel docking test platform is designed based on a general-purpose industrial manipulator using 3-D force and 3-D torque sensors. Different from the traditional solution, this novel platform is well-assembled and cost-effective. Furthermore, an actuation delay compensation method is introduced to improve the performance. Finally, the proposed method is evaluated using simulations. The results show that the novel method is with promising performance in terms of actuation delay compensation.